2012
DOI: 10.1038/onc.2012.546
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of cooperative NF-κB and Stat3 recruitment to ICAM-1 intronic consensus elements in the regulation of radiation-induced invasion and migration in glioma

Abstract: Although radiotherapy improves survival in patients, GBMs tend to relapse with augmented tumor migration and invasion even after irradiation (IR). Aberrant NF-κB and Stat3 activation and interaction has been suggested in several human tumors. However, possible NF-κB/Stat3 interaction and the role of Stat3 in maintenance of NF-κB nuclear retention in glioblastoma (GBM) still remain unknown. Stat3 and NF-κB (p65) physically interact with one another in the nucleus in glioma tumors. Most importantly, GST pull-dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 50 publications
6
113
0
Order By: Relevance
“…Irradiation also induced a dose-dependent increase in pSTAT3-Y705 nuclear accumulation in glioma xenografts (29). The above published data suggest that STAT3 activation might participate in influencing glioma sensitivity to radiotherapy.…”
Section: Concordant Studies Have Reported Signal Transducer and Activmentioning
confidence: 63%
See 2 more Smart Citations
“…Irradiation also induced a dose-dependent increase in pSTAT3-Y705 nuclear accumulation in glioma xenografts (29). The above published data suggest that STAT3 activation might participate in influencing glioma sensitivity to radiotherapy.…”
Section: Concordant Studies Have Reported Signal Transducer and Activmentioning
confidence: 63%
“…It also supports cell migration by augmenting MMP9 (51) and ICAM-1 (29) expression. It has been also shown that pSTAT3-Y705 activation in tumor cells participates in locally blocking immune cell maturation and activation by modifying tumor secretome (48).…”
Section: Concordant Studies Have Reported Signal Transducer and Activmentioning
confidence: 99%
See 1 more Smart Citation
“…As a major effector molecule of NF-kB activation through the STAT-3 pathway, IL-6 appears to be an important component of the NF-kB/IL-6/STAT-3 cascade involved in tumorigenesis [75]. STAT-3 is required for the maintenance of NF-kB activation in tumours [121], whilst IL-6 promotes carcinogenesis through inflammation and cell proliferation [35,44,106]. Since inflammation enhances the growth and progression of gastrointestinal tumours via the activation of IL-6-mediated STAT-3 signalling, it appears that there is a strong link between IL-6, inflammation and tumour promotion [1,117,118].…”
Section: Cancer-related Inflammationmentioning
confidence: 99%
“…Intercellular adhesion molecule-1 (ICAM-1/CD54) is an inducible cell-surface glycoprotein that mediates adhesion-dependent cellular interactions, and its high expression correlates with increased tumor malignancy and invasiveness. It was observed that irradiation significantly elevated nuclear phospho-p65/phospho-STAT3 interaction in correlation with increased intercellular adhesion molecule-1 (ICAM-1) and soluble-ICAM-1 levels, migration and invasion in human glioma cell lines [169].…”
Section: Invasionmentioning
confidence: 99%